PENERAPAN TEKNOLOGI BLOCK STORAGE DALAM SISTEM VIRTUALISASI BERBASIS OPENSTACK - Putri , Oka Karma; Irawan; Saharuna , Zawiyah (Politeknik Negeri Ujung Pandang, 2024)
In agriculture, the drip irrigation system is still using a manual system, so it is necessary to develop an automatic irrigation system that can make it easier for farmers to control water supply. network The use of wireless sensors in agriculture is a field that is experiencing an increase. Using a wireless network helps farmers when they have to carry out cable maintenance and repairs in areas that are difficult to reach. This study aims to implement a wireless sensor network based on ESP8266 for drip irrigation system automation that monitors changes in soil moisture and plant temperature, as well as automatic drip irrigation control. The method used in this study is the Waterfall Method, this model develops systematically from one stage to the next. The maximum range distance that can be achieved by the router node to send data to the sink node is 140 meters at the Line Of Sight (LOS) position. At the same time, the router node also controls drip irrigation automatically by sending commands to the actuator node (drip controller) to open or close the solenoid valve connected to the water reservoir which will circulate air by gravity. To implement it, you need ESP8266, YL-